Tailored protein encapsulation into a DNA host using geometrically organized supramolecular interactions - Andreas Sprengel (Nature Portfolio, 2017)
Current strategies for protein encapsulation in DNA vessels for controlled enzymatic catalysis or therapeutic delivery rely on formation of covalent complexes. Here, the authors design a system that mimics natural reversible non-covalent host–guest interactions between a DNA host and the protein DegP.